2019
DOI: 10.4103/jfmpc.jfmpc_465_18
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-based age estimation of illiac crests calcification in 10-29 year-old individuals

Abstract: Introduction: Estimating the age of the ossification of the iliac crest may help determine the legal age. For this purpose, both anthropological and radiological methods (conventional radiography, ultrasound, Tomography, and MRI) have been used to study different systems. Objectives: The present study aimed to to evaluate the iliac crest apophysis for age estimation through multidetector computed tomography (MDCT) in 10- to 29-year-old individuals. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previously undertaken CT-based investigations validate these advantages of computed tomography for age estimation. 2,26,35,37,52,64,69,[84][85][86] Comparative evaluations between computed tomography and plain radiography for iliac crest age estimation, too, have demonstrated that the overall repeatability and accuracy associated with CT supersedes that of X-ray examination. 52,64 Inter-and intra-observer error values computed within the present study demonstrate moderate to strong agreement between and within observers for CT-based iliac crest age estimation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously undertaken CT-based investigations validate these advantages of computed tomography for age estimation. 2,26,35,37,52,64,69,[84][85][86] Comparative evaluations between computed tomography and plain radiography for iliac crest age estimation, too, have demonstrated that the overall repeatability and accuracy associated with CT supersedes that of X-ray examination. 52,64 Inter-and intra-observer error values computed within the present study demonstrate moderate to strong agreement between and within observers for CT-based iliac crest age estimation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Within the pelvis, the iliac crest, a secondary ossification centre, displays a relatively longer development period and, thus, presents as a reliable age marker in sub-adults and young adults. 4,[23][24][25] Previously undertaken investigations with the iliac crest have indicated a good correlation between apophyseal ossification/ fusion changes and age, [26][27][28][29] signifying its utility as an age marker. Numerous scoring approaches for iliac crest ossification and fusion have been devised and researched in the past.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations